KREATIVITAS SANGGAR SANG CITRA BUDAYA SURAKARTA DALAM PELATIHAN TARI MASA PANDEMI COVID-19 - Hartanto (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2021)
ABSTRACT This report is the result of Community Service with the theme 'Creativity of the Surakarta Cultural Image Studio in Dance Training During the Covid-19 Pandemic.' The purpose of the training is to accommodate the talents, abilities and enrichment in the field of dance for the studio students. This training can foster the creativity of students in the field of dance. The targets of the activity are students and studio teachers. The training activities are carried out using the dialogical method, the lecture method, the demonstration method, and the drill method. The output of this activity is to direct and make students to develop creativity in learning dance. The result of the creativity training activity is the creation of the offerings dance "Sesaji Nur Citra Laksita" and Puppet Bocah "Dewa Ruci". This training provides an understanding of basic creativity, doing creative work, and to document audio-visual so that it can be used as a reference in learning dance at the Sanggar.